Innovative Civic Education Pedagogy for Strengthening Democracy and Character Formation: A Systematic Review (2017–2026) - Ananda Rauf Nurhidayah Isnaini (Master Kajian Literasi Kewarganegaraan, 2026)
This study addresses the growing concern over democratic fragility and the need for innovative civic education capable of strengthening democratic participation and character formation. The urgency of this research lies in responding to fragmented pedagogical approaches that often separate civic engagement, digital literacy, curriculum reform, and character development. This research employs a Systematic Literature Review guided by the PRISMA 2020 framework, analyzing 20 empirical journal articles published between 2017 and 2026 indexed in Scopus. The findings reveal four dominant pedagogical clusters: participatory and deliberative models, digital citizenship integration, curriculum and institutional reform, and character-integrated civic learning. Evidence indicates that experiential and dialogic approaches generate stronger democratic outcomes than knowledge-transmission models. The study concludes that democratic resilience is most effectively cultivated through an integrated pedagogical framework combining participation, ethical reflection, institutional support, and digital engagement.